C-reactive protein and its relation to high blood pressure in overweight or obese children and adolescents - Noronha, Juliana Andreia F. (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To investigate the association between C-reactive protein (CRP) and high blood pressure (BP) in overweight or obese children and adolescents. METHODS: Cross-sectional study with 184 overweight or obese children and adolescents aged from two to 18 years old, from April, 2009 to April, 2010. The classification of nutritional status used the body mass index (BMI). Based on the Centers for Disease Control and Prevention curve, individuals were classified as: overweight (BMI between the 85th-95th percentiles), obesity (BMI between 95(th)-97(th )percentiles) and severe obesity (BMI >97(th) percentile). Abnormal values were considered for systolic BP (SBP) and/or diastolic (DBP) if ≥90th percentile of the BP curve recommended for children and adolescents in the V Brazilian Guidelines on Hypertension, for waist circumference (WC) if ≥90th percentile of the curve established by the National Cholesterol Education Program, and for high sensitive CRP (hs-CRP) if >3mg/dL. To evaluate the association of inadequate values of CRP and the studied groups, chi-square test and analysis of variance were applied, using the Statistical Package for the Social Sciences version 17.0 and adopting a significance level of 5%. RESULTS: Among the evaluated sample, 66.3% were female, 63.5%, non-white, 64.1% had severe obesity, 78.3% had altered WC and 70.6% presented high BP. There was a significant association of CRP high levels with altered WC and BMI ≥97(th) percentile. In adolescents, high CRP was related to high SBP. CRP mean values were higher in individuals with elevated SBP. CONCLUSIONS: Inadequate values of hs-CRP were associated with severe obesity and high SBP in the studied population. These markers can be used to identify children and adolescents at higher risk for developing atherosclerosis.